Pengaruh Pemberian Reward Dan Punishment Terhadap Disiplin Kerja Karyawan : Sensus Pada Karyawan Bagian Produksi Jahit CV. Wijaya Family Tasikmalaya - Muhammad Razi Fiqri Hasani; Arga Sutrisna; Barin Barlian (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The purpose of this study was to determine simultaneously and partially the effect of reward and punishment on the work discipline of employees in the sewing production division of CV.Wijaya Family Tasikmalaya. The samples in this study were employees of CV. Wijaya Family Tasikmalaya, totaling 53 people. This research was conducted by collecting data with a questionnaire data collection technique, then testing the data with multiple linear regression analysis. The results of the study show that partially giving rewards has a significant effect on employee work discipline in the sewing production section of CV. Wijaya Family Tasikmalaya. Partially has a significant effect on punishment on employee work discipline in the sewing production section of CV. Wijaya Family TASIKMALAYA. Simultaneously, it has a significant effect on reward and punishment on employee work discipline in the sewing production section of CV. Wijaya Family Tasikmalaya.